2021
DOI: 10.1155/2021/4233615
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Screening and Potential Antibacterial Activity of Defatted and Nondefatted Methanolic Extracts of Xao Tam Phan (Paramignya trimera (Oliv.) Guillaum) Peels against Multidrug-Resistant Bacteria

Abstract: Xao tam phan (Paramignya trimera (Oliv.) Guillaum) is a traditional herbal medicine in Vietnam. Previous investigations reported mainly compounds and bioactivities of roots, stems, and leaves while there is limited information about those of fruits. This study aims to reveal the difference in the chemical profile of defatted peel (DP) and nondefatted peel (NDP) methanolic extracts of P. trimera using colorimetric reactions and liquid chromatography coupled with high-resolution mass spectrometry (LC-HRMS) analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…4 EOs have been reported to have various pharmacological effects such as powerful antibacterial, antifungal, anti-trichomonas, antioxidant, antiviral, anti-inflammatory, cytotoxic, and anticancer activities. 46,12,13 Recently, some scientists have reported that EOs from different plant parts inhibit enzymes related to diabetes and melasma skin such as α -amylase (eg, Eruca vesicaria subsp. longirostris , Mentha longifolia var.…”
Section: Resultsmentioning
confidence: 99%
“…4 EOs have been reported to have various pharmacological effects such as powerful antibacterial, antifungal, anti-trichomonas, antioxidant, antiviral, anti-inflammatory, cytotoxic, and anticancer activities. 46,12,13 Recently, some scientists have reported that EOs from different plant parts inhibit enzymes related to diabetes and melasma skin such as α -amylase (eg, Eruca vesicaria subsp. longirostris , Mentha longifolia var.…”
Section: Resultsmentioning
confidence: 99%
“…The alkaloids identification was by adding the Dragendroff, Bouchardat and Meyer reagents to the test tube. The formation of orange to reddish, brown and white to yellowish was the sign of alkaloids presence, respectively ( 12 , 13 ). The flavonoids identification was by adding 0.1 mg of magnesium powder, 1 ml of amyl alcohol and hydrogen chloride to the test tube.…”
Section: Methodsmentioning
confidence: 99%
“…The glycosides identification was by mixing 5 ml of extract and 25 ml of H 2 SO 4 , then heated to boiling points for 15 minutes then cooled and added NaOH, next with 5 ml Fehling solution. The formation of red brick indicated the presence of glycosides ( 12 ). Saponins identification by heating the extract to its boiling point then shake until the formation of foam layer that indicated the presence of saponins ( 13 ).…”
Section: Methodsmentioning
confidence: 99%
“…The alkaloids in the extract formed a reddish (Dragendorff reagent), brown (Bouchardat reagent) and white to yellowish (Meyer reagent) color in the test tube. 11,12 To identify the glycosides, we started by addition of 25 ml of H 2 SO 4 to 5 ml of extract then boiled for 15 minutes. After the mixture cooled off , NaOH and 5 ml Fehling solution added and red brick color formation indicated the presence of glycosides.…”
Section: Phytochemical Screeningmentioning
confidence: 99%